Variabilidade pluviométrica na área paulista da bacia hidrográfica do rio Ribeira de Iguape (Brasil) e a influência do ENOS, a partir da técnica Box-Plot - Valéria Machado Emiliano; Nádia Gilma Beserra de Lima; Jakeline Baratto; Emerson Galvani (Terr@ Plural)
An analysis of monthly rainfall was carried out during years influenced by the El Niño-Southern Oscillation (ENSO) phenomena in the Ribeira de Iguape Valley, located in the southeast of the state of São Paulo. Data from 1970 to 2017 from 18 rainfall stations distributed across the upper, middle and lower reaches of the Ribeira de Iguape river were analyzed using the Box-Plot methodology to identify monthly standard years. A water surplus was observed in precipitation during years influenced by ENSO, while in years influenced by La Niña phenomena (LA) there was greater variability in rainfall. In many ENSO years, surpluses occurred mainly in spring (October, November and December) and late summer (January, February and March). In the LA phase, droughts were more evident in the spring (September and October) and in the months of February and March. It is concluded that the phenomenon in the region presents monthly variability and does not follow a constant and spatially regular pattern. Therefore, it is necessary to analyze and understand other atmospheric phenomena, such as cold fronts, the Southern Annular Mode (MAS), the South Atlantic Dipole, and the EN Canônico/Modoki, among others, which can influence the dynamics of rainfall in the region.